Biological Characteristics and Carrier Functions of Pegylated Manganese Zinc Ferrite Nanoparticles. (18th November 2019) - Guo, Ting; Dou, Fengxiao; Lin, Mei; Huang, Junxing; Zhou, Chenglin; Zhang, Jun; Yu, Hong; Jiang, Xingmao; Ye, Jun; Shi, Yujuan; Xiao, Yanhong; Bian, Xuefeng; et al.
Abstract : This study was performed to investigate the biocompatibility (BC), magnetothermal effect, and DNA binding biological characteristics of manganese zinc ferrite nanoparticles (Mn0.6 Zn0.4 Fe2 O4 -NPs (MZF-NPs)) coated with pegylated manganese (PEG-MZF-NPs). Their functions as gene transfer carrier for gene therapy and magnetic medium for tumor hyperthermia were also explored. The manganese zinc ferrite nanoparticles were synthesized through high temperature cracking, and their characterizations were discovered. Hemolysis test and MTT assay were performed to evaluate biocompatibility, and their self-heating effects in the alternating magnetic field were investigated. PEG-MZF-NPs with different concentrations were measured by using 7.0 T Micro-MR scanner (MRI) to calculate the T2 value and r2 relaxation rate of each sample. The CD44-shRNA plasmids were constructed, and their ability to bind PEG-MZF-NPs were examined. The DNA release from PEG-MZF-NP/DNA complex and protection of DNA from nuclease digestion were also detected. After CD44-shRNA-EGFP were transfected into the ovarian cancer SK-OV-3 cells by using PEG-MZF-NPs as carriers, the transfection efficiency was detected by a flow cytometer and expression of CD44 mRNA and protein in cells was detected using RT-PCR and Western blot, respectively. We successfully prepared PEG-MZF-NPs with favorable dispersity, magnetic responsiveness, and BC. Typically, the excellent magnetothermal effect can be used for a tumor magnetothermal therapeutic study. In vitro MRI showed the application potential for being magnetic resonance T2 relaxation contrast agents and the possibility to achieve goal of integration of targeting diagnosis and treatment. The CD44-shRNA plasmids have been successfully constructed and concluded that PEG-MZF-NPs may serve as gene transfer carriers for gene therapy.